Cytological evaluation by Caco-2 and KU812 of non-allergenic peptides from simulated digestion of infant formula in vitro - Zihao Xu; Hao Bai; Xin Ma; Yong Wu; Zhihua Wu; Anshu Yang; Weixiang Mao; Xin Li; Hongbing Chen (Food Science and Human Wellness)
Milk allergy is a common allergic reaction found in infants and young children, most of them appear tolerance after growing up. In this study, infant formula was digested by simulated in vitro digestion method. The potential non-allergenic peptides were further screened from undigested products by exclusion of the known epitopes from β-lactoglobulin (BLG) and α-lactalbumin (ALA). These potential non-allergenic peptides were synthesized and their transferability were determined by Caco-2 cell monolayer model. Finally, the potential allergenicity were evaluated by KU812 cell degranulation model. The results showed that 7 peptides were screened as non-allergenic sequences, among which were 3 from ALA and 4 from BLG. The Caco-2 cell model showed that all the synthetic peptides were absorbed and transported well. However, only peptide BLG107-118 showed potential allegencity by KU812 model. In conclusion, six peptides, including ALA29–51, ALA80–90, ALA94–103, BLG1–20, BLG24–50, and BLG123–139 were evaluated as hypoallergenic peptides, which could be used for candidates of peptides inducing immune tolerance for persons with milk allergy.